Estimating the burden of musculoskeletal disorders in the community: the comparative prevalence of symptoms at different anatomical sites, and the relation to social deprivation. Issue 11 (1st November 1998) - Urwin, Michelle; Symmons, Deborah; Allison, Timothy; Brammah, Thérèse; Busby, Helen; Roxby, Morven; Simmons, Alicia; Williams, Gareth
Abstract : BACKGROUND: Epidemiologically-based rheumatology healthcare needs assessment requires an understanding of the incidence and prevalence of musculoskeletal disorders in the community, of the reasons why people consult in primary care, and of the proportion of people who would benefit from referral to secondary care and paramedical services. This paper reports the first phase of such a needs assessment exercise. SPECIFIC OBJECTIVE: To estimate the relative frequency of musculoskeletal pain in different, and multiple, anatomical sites in the adult population. SETTING: Three general practices in the former Tameside and Glossop Health Authority, Greater Manchester, UK, a predominantly urban area. DESIGN: Population survey. METHODS: An age and sex stratified sample of 6000 adults from the three practices was mailed a questionnaire that sought data on demographic factors, musculoskeletal symptoms (pain in the past month lasting for more than a week), and physical disability (using the modified Health Assessment Questionnaire- mHAQ). The areas of pain covered were neck, back, shoulder, elbow, hand, hip, knee, and multiple joints. The Carstairs index was used as a measure of social deprivation of the postcode sector in which the person lived. RESULTS: The response rate after two reminders was 78.5%. Non-responders were more likely to live in areas of high social deprivation. People who lived in more deprived areas were also more likely to report musculoskeletal pain, especially backpain. After adjusting for social deprivation the rates of musculoskeletal pain did not differ between the practices and so their results were combined. After adjustment for social deprivation, the most common site of pain was back (23%; 95% CI 21, 25) followed by knee (19%; 95% CI 18, 21), and shoulder (16%; 95% CI 14, 17). The majority of subjects who reported pain had pain in more than one site. The prevalence of physical disability in the community rose with age. It was highest in those with multiple joint problems but was also high in those with isolated back or knee pain. CONCLUSION: Musculoskeletal pain is common in the community. People who live in socially deprived areas have more musculoskeletal symptoms. Estimates of the overall burden of musculoskeletal pain that combine the results of site specific surveys will be too high, those that do not adjust for socioeconomic factors will be too low.